Uma vida feminina: a personagem Biela de Uma vida em segredo, de Autran Dourado - Simonetti, Marivane (2021)
In this work, we investigated the character Biela, protagonist of A hiddenlife(Autran Dourado, 1964). This novel, placed in Minas Gerais at the beginning of the 20th century, tells the story of Biela, a countrysidegirl who moves to the city, at the age of eighteen, and needs to adapt to new customs there. Biela represents a white and wealthy woman who does not fit the standards required by society. It is sought, from that, to discuss the relationship between the social role of women and male domination that permeates a society in which some values of patriarchy still remain. The research consists of a bio-bibliographic survey and critical reception about the writer and his work, the study of character and some discussions about the female condition in society still with patriarchal features. Regarding the discussions about character, we used, among others, Candido (1987; 2010), Brait (1985), Forster (2005). These authors start from the concept of character in order to study their role played in a novel in addition to tracing approaches on the expression of the character as what is most real in a narrative. The theoretical contribution is based mainly on the categories of Reis (1987) nucleus and nebula, which respectively define the hierarchical social organization around a male power figure (nucleus) contrasting with the marginalized characters around him (nebula). We also have the theoretical contributions of Bourdieu (2012), whose reflections point out that social formation through male domination remains in our society in a way of a symbolic violence, the one that, despite being non-physical, forms our structures of thoughts and justifies the position of women as non-subjects, a concept also defended by Beauvoir(1967; 1970). In addition, our theoretical framework relies on Lepecki (1976) who analyzes the works of Autran Dourado from a mythical and psychoanalytic perspective. Composed by the understanding of the writer and his work, the study of the character andthe situation of women in a society with patriarchal marks, this dissertation aims to demonstrate how Biela is an element of subversion within a society still marked by the patriarchal logic and oppression when the protagonist refuses to fulfill certain expectations and privileges of the socio-economic class to which she belongs, preferring to live in a place between the periphery and the center from which the exercise of power derives.